Regulatory mechanisms of GCN5 in osteogenic differentiation of MSCs in periodontitis - Wei Lu; Li Zhang; Kun Ji; Ling Ding; Guofeng Wu (Wiley, 2023)
Abstract Objectives The regulatory mechanisms of GCN5 (General control non‐repressed protein5) in the osteogenic differentiation of mesenchymal stem cells (MSCs) in periodontitis are still unclear. The purpose of this review focuses on the regulating roles of GCN5 in bone metabolism and periodontitis, discusses the potential molecular mechanism and provides targets and new ideas for the treatment of periodontitis. Material and Methods The integrative review methodology was used. Data sources include PubMed, Cochrane Library, and additional sources. Results MSCs play an important role in the osteogenesis balance of periodontal tissue. Periodontal ligament stem cells (PDLSCs) from periodontitis patients exhibited defective osteogenic differentiation capacities. Histone acetylation is important in regulating the differentiation of different types of MSCs cells and is closely related to the reduced osteogenic differentiation of PDLSCs. GCN5, one of the first histone acetyltransferase linked to gene transcriptional activation, participates in many biological processes of mesenchymal stem cells. Downregulation of GCN5 expression and lack of GCN5 caused decreased osteogenic differentiation of PDLSCs. Intercellular information exchange may be an important way for MSCs to exert their regulatory and therapeutic functions. Conclusions GCN5 affects the function of cell metabolism‐related genes by regulating the acetylation status of histones or non‐histones, thereby regulating some important progress of MSCs such as PDLSCs' osteogenic differentiation and BMCS osteogenic differentiation.